Surface passivation of black silicon phosphorus emitters with atomic layer deposited SiO2/Al2O3 stacks. (September 2017) - Pasanen, Toni; Vähänissi, Ville; Theut, Nicholas; Savin, Hele
Abstract: Black silicon (b-Si) is a promising surface structure for solar cells due to its low reflectance and excellent light trapping properties. While atomic layer deposited (ALD) Al2 O3 has been shown to passivate efficiently lightly-doped b-Si surfaces and boron emitters, the negative fixed charge characteristic of Al2 O3 thin films makes it unfavorable for the passivation of more commonly used n + emitters. This work studies the potential of ALD SiO2 /Al2 O3 stacks for the passivation of b-Si phosphorus emitters fabricated by an industrially viable POCl3 gas phase diffusion process. The stacks have positive charge density (Qtot = 5.5·10 11 cm -2 ) combined with high quality interface ( D it = 2.0·10 11 cm -2 eV -1 ) which is favorable for such heavily-doped n-type surfaces. Indeed, a clear improvement in emitter saturation current density, J 0e, is achieved with the stacks compared to bare Al2 O3 in both b-Si and planar emitters. However, although the positive charge density in the case of black silicon is even higher ( Q tot = 2.0·10 12 cm -2 ), the measured J0e is limited by the recombination in the emitter due to heavy doping of the nanostructures. The results thus imply that in order to obtain lower saturation current density on b-Si, careful optimization of the black silicon emitter profile is needed.